Characterization of the Kinetics of Cardiac Cytosolic Malate Dehydrogenase and Comparative Analysis of Cytosolic and Mitochondrial Isoforms - Dasika, Santosh K. (Biophys J, 2015)
Because the mitochondrial inner membrane is impermeable to pyridine nucleotides, transport of reducing equivalents between the mitochondrial matrix and the cytoplasm relies on shuttle mechanisms, including the malate-aspartate shuttle and the glycerol-3-phosphate shuttle. These shuttles are needed for reducing equivalents generated by metabolic reactions in the cytosol to be oxidized via aerobic metabolism. Two isoenzymes of malate dehydrogenase (MDH) operate as components of the malate-aspartate shuttle, in which a reducing equivalent is transported via malate, which when oxidized to oxaloacetate, transfers an electron pair to reduce NAD to NADH. Several competing mechanisms have been proposed for the MDH-catalyzed reaction. This study aims to identify the pH-dependent kinetic mechanism for cytoplasmic MDH (cMDH) catalyzed oxidation/reduction of MAL/OAA. Experiments were conducted assaying the forward and reverse directions with products initially present, varying pH between 6.5 and 9.0. By fitting time-course data to various mechanisms, it is determined that an ordered bi-bi mechanism with coenzyme binding first followed by the binding of substrate is able to explain the kinetic data. The proposed mechanism is similar to, but not identical to, the mechanism recently determined for the mitochondrial isoform, mMDH. cMDH and mMDH mechanisms are also shown to both be reduced versions of a common, more complex mechanism that can explain the kinetic data for both isoforms. Comparing the simulated activity (ratio of initial velocity to the enzyme concentration) under physiological conditions, the mitochondrial MDH (mMDH) activity is predicted to be higher than cMDH activity under mitochondrial matrix conditions while the cMDH activity is higher than mMDH activity under cytoplasmic conditions, suggesting that the functions of the isoforms are kinetically tuned to their individual physiological roles.